Soil quality assessment and climatic condition of selected forest reserves in Terengganu, Malaysia - Karam Singh, Daljit Singh; Johari, Muhammad Iqbal Hakim; Mohd Ibrahim, Mohd Hakeem; Mohamed Zulperi, Dzarifah (Malaysian Society of Soil Science, 2024)
This study was conducted across selected forest reserves in Terengganu, namely Jambu Bongkok, Merchang, Pelagat, and Bukit Kesing, with the aim of addressing the conservation needs of endangered timber tree species, specifically within the Dipterocarpaceae family. The research emphasizes the urgent need for comprehensive data to enhance conservation strategies for Terengganu's valuable timber species. By evaluating the soil quality and its climatic current status, the project provides crucial tools for the Terengganu Forestry State Department to implement effective conservation measures. Soil quality assessments, based on Amacher et al. (2007), indicated that coarse fragment content generally does not adversely affect soil quality in the forest reserves, except for Merchang. Compaction levels were found to be very low across all reserves, consistent with the characteristics of undisturbed tropical forests. The Soil Quality Index (SQI) varied from 15.79% to 26.32%, with Jambu Bongkok exhibiting low SQI due to its sandy soil, low cation exchange capacity, and low water-holding capacity.